The Role of The Board of Commissioners in Moderating the Effect of Information Asymmetry on Earnings Management - Ming Chen; Heriyanto Heriyanto (Faculty of Economics dan Business, Atma Jaya Makassar University, 2023)
The purpose of this study is to empirically examine the role of the board of commissioners in moderating the relationship of information asymmetry to earnings management. This study uses secondary data and measurement in this study consists of the size of the board of commissioners measured by the number of proportions of the board of commissioners, earnings management is measured using the modified Jones model, and information asymmetry is measured using the bid ask spread. The sample in this study are manufacturing companies listed on the IDX in 2019-2021. Testing the data in this study using Moderate Regression Analysis (MRA) and SPSS 23.0 as a testing tool. The results in this study are that the board of commissioners is not able to moderate the relationship of information asymmetry to earnings management, this is because this is due to several factors and this study shows that the size of the board of commissioners is still below 30 percent which indicates that the duties and responsibilities carried out by the board of commissioners in supervising and controlling management actions.